Current Research of Trichinellosis in China - Bai, Xue; Hu, Xiaoxiang; Liu, Xiaolei; Tang, Bin; Liu, Mingyuan (Frontiers in Microbiology, 2017)
Trichinellosis, caused by Trichinella, is an emerging or re-emerging zoonotic parasitic disease, which is distributed worldwide with major socio-economic importance in some developing countries. In particular, it has been estimated that more than 40 million people are at risk of Trichinella infection in China. This review summarizes the current information on the epidemiology, laboratory diagnosis and vaccines of trichinellosis in China. Moreover, study of the treatment potential of using Trichinella for immune-related diseases and cancer, as well as the transcription and post-transcription modification of Trichinella were also collected, providing perspectives for future investigations. These advances in research are expected to aid the development of new strategies for the prevention and control of trichinellosis and may potentially yield biological agents for treating other diseases.